Nursing informatics : scope and standards of practice - American Nurses Association (Silver Spring, MD : American Nurses Association, 2022)
'Nursing Informatics: Scope and Standards of Practice describes a competent level of nursing care at each level of nursing informatics practice and provides comprehensive overviews of the dynamic and complex practice of the nursing informatics specialty. Published by ANA, this book is informed by advances in health care and professional nursing practice. It contains national standards of practice and performance that define the who, what, where, when, why, and how of nursing informatics practice and is a vital reference for: - Quality improvement initiatives - Certification and credentialing - Position descriptions and performance appraisals - Classroom teaching and in-service education programs - Boards of nursing members' orientation programs and regulatory decision-making activities Nursing Informatics: Scope and Standards of Practice is intended to guide nurses, as well as administrators, legislators, regulators, legal counsel, and other interprofessional colleagues'--
Scope of nursing informatics practice -- Standards of nursing informatics practice -- Standards of professional performance for nursing informatics.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 12, 2022).
Added to collection customer.56279.3
Keywords: Vocational qualifications; Nursing Informatics -- standards; Nursing Informatics -- methods; Professional Competence; Qualifications professionnelles; Vocational qualifications